Cultural translation of the ethical dimension: a study on the reliability and validity of the Chinese nurses' professional ethical dilemma scale - Wei Hu; Ke Shang; Xin Wang; Xia Li (BMC, 2024)
Abstract Background Quantifying the professional ethical challenges that nurses encounter is crucial for both theoretical insights and practical outcomes. The objective of this research is to assess the psychometric properties of the Chinese adaptation of the Moral Distress Scale for Healthcare Professionals (MD-APPS). Methods In 2024, a survey approach was utilized to engage with several tertiary-level healthcare institutions throughout China. A cohort of 448 nursing professionals who satisfied the specified selection benchmarks was consequently incorporated into the study. To evaluate the scale's reliability and validity, methods including the Content Validity Index (CVI), Factor Analysis-both Exploratory (EFA) and Confirmatory (CFA)-alongside assessments of internal consistency and test-retest reliability were employed. Results Expert evaluations yielded an I-CVI of 0.90, suggesting good content validity for the MD-APPS's Chinese adaptation. Exploratory Factor Analysis (EFA) revealed a bi-dimensional framework with 7 components, explaining 56.34% of the cumulative variance. Confirmatory Factor Analysis (CFA) outcomes displayed a χ-square/df ratio of 1.542. The estimate for Robust RMSEA was 0.054, and the SRMR was ascertained to be 0.041. Indices for both Robust TLI and Robust CFI surpassed the 0.9 threshold, indicating an acceptable fit; this aspect was supported by a P-value (Chi-square) of 0.094. The internal consistency, measured by Cronbach's α, was found to be 0.74, while the test-retest reliability over a two-week period reached 0.964. These findings provide initial evidence for the psychometric properties of the Chinese MD-APPS. Conclusion The Chinese adaptation of the MD-APPS demonstrates promising initial psychometric properties, suggesting its potential suitability for exploring nurses' professional ethical challenges within the Chinese cultural context. This scale may facilitate the identification of diverse elements influencing nurses' professional ethics and the assessment of the ethical climate in nursing practices. However, further validation studies are needed to fully establish its psychometric robustness across various healthcare settings in China.